Implementasi Program Edukasi Anti-Perundungan sebagai Upaya Pembentukan Karakter Peserta Didik SMPN 2 Tanjung Bintang Kabupaten Lampung Selatan - Rojiati, Umi; Bakri, Aflahghazi Marpen; Wulandari, Aghnes; Permana, Andika; Pratiwi, Fajaria Hera (Journal of Smart Community Service, 2025)
Bullying remains a critical issue in Indonesian schools, affecting students’ well-being and academic performance. This community service was conducted at SMPN 2 Tanjung Bintang, South Lampung, to implement an anti-bullying education program as part of character development. The program involved 150 students from grades 7 to 9 and consisted of three phases: material presentation, empathy-building through case reflections, and simulation using video-based role reversals. Activities included lectures, discussions, and reflective storytelling. Post-program evaluation showed improvements in students' ability to identify bullying, increased empathy, and courage to act against injustice. The belief that bullying is normal dropped from 74% to 19%. This initiative not only raised awareness but also encouraged ethical behavior, aligning with national character education values. The program proved effective and replicable in fostering safe and inclusive school environments.